"Between a Rock and a Hard Place": The Constraints of Welfare‐to‐Work Bureaucracies. Issue 1 (9th March 2018) - Gross, Christi L.; Church, Jacob; Taylor, Tiffany; Towne‐Roese, Jackuelyn K.
Abstract : Using data drawn from telephone interviews with program managers in Ohio's welfare‐to‐work program, Ohio Works First (OWF; N  = 69), we examine how managers deal with revisions to welfare‐to‐work program requirements. Specifically, we examine the tensions concerning expectations that managers will both police and help clients. Much like street‐level bureaucrats, managers not only face these tensions, but they also supervise caseworkers to ensure county compliance with government rules. Therefore, we also examine managers' frustrations with state and federal governments, their clients, and the bureaucratic constraints associated with their positions.